1984
DOI: 10.1139/g84-086
|View full text |Cite
|
Sign up to set email alerts
|

Inversion polymorphisms in natural populations of Anopheles stephensi

Abstract: A preliminary survey of natural populations of Anopheles stephensi Liston in Pakistan has uncovered the presence of 16 autosomal paracentric inversions. Twelve previously undescribed inversions were observed in the field populations and an additional new one was seen in a laboratory colony. A comparison of urban and rural populations showed striking differences in the kinds and frequencies of paracentric inversions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 2 publications
2
38
0
Order By: Relevance
“…Chromosome arm 3R shows the sections 26, 27, 28, 29, 30, 33, and 34, which were subdivided into 3, 3, 4, 3, 3, 3, and 3 subsections, respectively. In the chromosome arm 3L, sections 36,37,38,39,40,41,42,43, and 44 were subdivided into 4, 4, 4, 3, 3, 4, 4, 4, and 3 subsections, respectively. Other sections in which not all chromosome arms were modified, the number of subdivisions was maintained according to the reference map.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosome arm 3R shows the sections 26, 27, 28, 29, 30, 33, and 34, which were subdivided into 3, 3, 4, 3, 3, 3, and 3 subsections, respectively. In the chromosome arm 3L, sections 36,37,38,39,40,41,42,43, and 44 were subdivided into 4, 4, 4, 3, 3, 4, 4, 4, and 3 subsections, respectively. Other sections in which not all chromosome arms were modified, the number of subdivisions was maintained according to the reference map.…”
Section: Resultsmentioning
confidence: 99%
“…In this latter mosquito, genetic studies indicated chromosomal positions for the breakpoints of the 19 paracentric inversions. 28,42,43 In addition, polymorphic inversions are not distributed evenly across the A. stephensi genome. More than two-thirds of them are distributed among two arms, such as five inversions are on 2R and nine on 3L.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal studies of the Asian malaria vector An. stephensi reveal striking differences in the kinds and frequencies of paracentric inversions on 2R and 3L between rural and urban populations, especially with respect to the common 2Rb inversion [16]. These observations suggest that the genes on the 2R and 2L arms of An.…”
Section: Introductionmentioning
confidence: 99%
“…For example, chromosome arms 3R and 3L of An. gambiae and homologous arms in other mosquito species have the lowest rates of inversion polymorphism and fixation [11,13,16,18]. The low tolerance of a chromosome to gene order disruption could contribute to the low rate of inversion establishment.…”
Section: Introductionmentioning
confidence: 99%
“…The variety mysorensis and type forms can also be discriminated at adult stage based on their thoracic spiracle length and its index (Nagpal et al 2003). All three forms can also be differentiated through types and frequencies of paracentric inversions (Coluzzi et al 1973;Mahmood and Sakai 1984;Subbarao et al 1987). Despite cytotaxonomic differences, cross-mating experiments between these forms failed to establish them as cryptic species and, thus, they are best considered as local population variants (Davidson and Jackson 1961;Rutledge et al 1970;Subbarao et al 1987;Sweet et al 1938).…”
Section: Introductionmentioning
confidence: 99%